2020
DOI: 10.1177/1557988319892437
|View full text |Cite
|
Sign up to set email alerts
|

Zulu Men’s Conceptions, Understanding, and Experiences of Voluntary Medical Male Circumcision in KwaZulu-Natal, South Africa

Abstract: Voluntary Medical Male Circumcision (VMMC) is proven to reduce transmission of HIV/AIDS. Despite concerted efforts to scale up VMMC in men aged 18–49, the number of medically circumcised men in this age group remains suboptimal. Research has shown that several individual factors hinder and promote uptake of VMMC. The nature of these factors is not clearly understood within the dimensions of religion, culture and tradition, particularly in a low-income rural setting. This study aimed to analyze Zulu men’s conce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Given the low incidence of HIV in CNC after CVCT, cost-benefit analyses preclude PrEP in this group. Similarly, given limited access and low uptake in many areas [ [72] , [73] , [74] ] men in concordant HIV- unions would be a lower programmatic priority for male circumcision compared with single men or men with HIV + spouses.…”
Section: Discussionmentioning
confidence: 99%
“…Given the low incidence of HIV in CNC after CVCT, cost-benefit analyses preclude PrEP in this group. Similarly, given limited access and low uptake in many areas [ [72] , [73] , [74] ] men in concordant HIV- unions would be a lower programmatic priority for male circumcision compared with single men or men with HIV + spouses.…”
Section: Discussionmentioning
confidence: 99%
“…24 , 25 , 26 Research on the socio-cultural barriers affecting uptake VMMC among men has revealed that culture and religion can act as both barriers and drivers to the acceptability of medical circumcision by men. 12 , 27 Alluding to the cultural barriers affecting VMMC among men, Nxumalo and Mchunu 28 found that cultural and religious norms were a major influences for uptake of VMMC among Zulu men in KZN, South Africa. The present study’s finding that healthcare workers’ perceptions of VMMC are influenced by cultural dynamics is significant as it highlights the deep-rooted influence of the socio-cultural context on healthcare and health service delivery.…”
Section: Discussionmentioning
confidence: 99%
“…The conception of VMMC as being unnatural, unnecessary and sinful were some of the competing norms found in study, which informed the development of the present model. 28 …”
Section: Methodsmentioning
confidence: 99%
“…Similarly other studies conducted on the acceptability of medical circumcision have shown that healthcare workers (HCWs) and female partners are major influencers in terms of a man’s decision to undergo VMMC. 27 , 28 Studies exploring female partners’ role in the uptake of VMMC have revealed their view of a circumcised man being more aesthetically appealing and masculine were motivators for men to undergo medical circumcision. 29 , 30 From a healthcare perspective, it is postulated that the main barrier to the successful scale-up of VMMC in the priority countries is demand creation, so an understanding of the contextual barriers and facilitators for VMMC is crucial for demand creation.…”
Section: Introductionmentioning
confidence: 99%